Surgical Site Infection Post Caesarean Section: A Case Report - Hartati; Febi Stevi Aryani; M Satria Erlangga Sinum; Emasrissa Murwani (HM Publisher, 2021)
Background. Surgical site infection (SSI) is a major complication of surgery which can increase morbidity, mortality and cost of hospitality. Incidence of SSI at a healthcare provider/facility reflected a service quality of that institution. Case presentation. A 28-years-old woman, a housewife, P2A1, post-caesarean section 12 days ago. Pasien datang dengan keluhan utama badan lemas dan terdapat nanah pada luka bekas operasi. Ia mengeluh perutnya terasa semakin panas, dan keluar cairan bening sebelum muncul nanah pada luka operasi. Pasien juga mengeluh demam, mual dan lemas akhir-akhir ini Laboratory investigations showed Hb 11,9 g/dL, Leukosit 11.100 m/L, trombosit 601.000. MCV 70,7 fL MCH 24 pg MCHC 32 g/dL TIBC 392 mg/dL serum Iron 54 mg/dL Ferritin 19,8 ng/mL, CRP reactive. Patient was wound dressing and given levofloxacin 500mg three times a day intravascular for three days and continue with ciprofloxacin three time a day oral. Patient was suggest to repeat laboratory test after therapy to evaluate therapy response. Conclusion: The result showed that time of prophylactic antibiotics can used to minimize the occurrence of SSI in post-caesarean section patients.